Attendance and non-attendance for breast screening at the south east London breast screening service. Issue 6691 (8th July 1989) - McEwen, J.; King, E.; Bickler, G.
Abstract : OBJECTIVES--To ascertain the reasons for a low rate of response for breast screening. DESIGN--All relevant aspects of the organisational process examined, including general practitioners' notes. Non-responders visited and interviewed. SETTING--An inner city breast screening service working on the model advocated by the Forrest report. SUBJECTS--288 Women aged 50-64 registered with several general practices and invited for screening by post. MAIN OUTCOME--Determination of factors important for success of breast screening programmes. RESULTS--After five women were excluded by their general practitioners the response rate was 129 out of 283 (46%), but 99 (35%) of the women did not receive their invitations because of inaccuracies in the family practitioner committee's database and general practitioners failing to check women's addresses completely. CONCLUSIONS--Increased rates of response will depend on enabling general practitioners to check addresses and on an increased awareness of the importance of information.